The predictive accuracy of hypoxic scoring for prediction of adverse outcome in neonates born with asphyxia - Saqib, Muhammad; Jamil, Safeer A.; Arif, Usman; Anwar, Zubda; Waheed, Sarosh; Bashir, Munibah; Javed, Maham (International Journal of Contemporary Pediatrics, 2020)
Background: Birth asphyxia is a major contributor to neonatal mortality. Fetal hypoxia followed by asphyxia is common cause of brain injury in term infants. Hypoxia score has shown to be accurate enough to predict adverse outcome in asphyxiated neonates. But controversies exist regarding predictive accuracy of hypoxia score. So we conducted this study. Objective to assess the predictive accuracy of hypoxic scoring for prediction of adverse outcome in neonates born with asphyxia. Methods: 170 neonates were screed for hypoxia score. Neonates were labelled as positive or negative. Then all neonates were followed-up for 7 days. If neonate died within 7days, then case was confirmed as positive or negative. Data was analysed by using SPSS 20. 2x2 table was developed to calculate sensitivity, specificity, PPV, NPV and predictive accuracy of hypoxia score. Results: The mean Apgar score at birth was 5.01±0.83. The sensitivity of hypoxia score was 87.8%, specificity was 90.9%, PPV was 90%, NPV was 88.9% while predictive accuracy was 89.4% taking actual adverse outcome as gold standard. Conclusions: The predictive accuracy of hypoxia score was high for prediction of adverse outcome in asphyxiated neonates.